Figure 2 from: Larraín J (2016) The mosses (Bryophyta) of Capitán Prat Province, Aisén Region, southern Chile. PhytoKeys 68: 91-116. https://doi.org/10.3897/phytokeys.68.9181 - Larraín, Juan (Zenodo, 2016)
Figure 2 - Different habitats of Capitán Prat. A Steppe at Estancia Chacabuco B Nothofagus dombeyi–Nothofagus antarctica–Pilgerodendron uviferum forest at Lago Vargas C Nothofagus dombeyi–Drimys winteri–Podocarpus nubigenus forest at Río Bravo D Peatland at Lago Leal.